Study on the strength characteristics and micro-mechanism of modified solidified red mud - Ding, Ziyi; Cheng, Yu; Jin, Lu; Wang, Wentong; Yan, Shiying (Frontiers in Materials, 2024)
The residue generated during the production process of alumina, known as red mud, is a type of solid waste. The engineering properties of red mud can be significantly enhanced through the modification and solidification using inorganic materials. This study primarily utilized red mud as the raw material, supplemented with fly ash, lime, and clay, to conduct a solidification experiment of red mud. Orthogonal tests with three factors of two ash ratio (ratio of lime to fly ash), two ash content (total lime and fly ash), and red mud types were designed to study the changes of different ratios and maintenance conditions, etc., on the engineering properties of red mud. In addition, the micro-mechanisms of modified red mud were investigated by means of XRF, XRD, SEM and EDX. The results show that for optimum moisture content, red mud types are the most important influencing factor and for maximum dry density, two ash content is the most important influencing factor. For strength characteristics, the optimum two ash ratio was 1.5:1, the optimum two ash content was 50%, and the optimum red mud types were 70% CRM (red mud made of Chalco Shandong Co., Ltd) mixed with 30% clay. The addition of lime, fly ash, and clay improves the temperature shrinkage coefficient of the red mud. Through the analysis of microscopic composition and structure, it can be seen that goethite (α-FeO(OH)) and magnetite (γ-Fe2O3) in the red mud reacted with the modified materials to generate crystalline aluminosilicate and amorphous hydrated silicate gel, and these products together with the original calcium carbonate (CaCO3), tricalcium aluminate (Ca3Al2O6) and garnet (Ca3TiFeSi3O12) in the red mud which have certain strengths enhance the structural strength of the modified red mud. The optimum ratio obtained from the combined test results was lime: fly ash: CRM = 30:20:50.